P-342 The impact of Clomiphene Citrate (CC) on the endometrium in comparison to gonadotropins (Gn) in intrauterine-insemination treatments (IUI): Is it thinner and does it matter?. (30th June 2022) - Lu, Y; Cherouveim, P; Jiang, V; Dimitriadis, I; Bormann, C; James, K; Souter, I
Abstract: Study question: Utilizing patients as their own controls, does endometrial thickness (EMT) differ between CC/IUI and Gn/IUI? Does EMT differ between CC-cycles with and without associated conception? Summary answer: Within-patient, CC resulted in thinner EMT compared to Gn. CC-cycles associated with conception compared to the ones without it, had thicker endometria. What is known already: CC, unlike gonadotropins, may have an anti-estrogenic effect on the endometrium. Concerns exist that the thinning of the endometrium might be associated with altered endometrial development and receptivity. However, available data in CC cycles remain inconsistent, probably due to patient and protocol heterogeneity. Currently, it remains unclear whether CC treatments produce a thinner endometrium, compared to gonadotropins, in the same patient. Furthermore, it is uncertain whether such a difference, if one exists, has a consequential effect on IUI cycle outcomes. Study design, size, duration: Design: retrospective. Duration: 1/2004-9/2021 Cohort 1 utilized women as their own controls to evaluate CC's impact on the endometrium and included all cycles from women who sought fertility treatments and initially underwent CC/IUI (CC1, n = 1252) followed by Gn/IUI (Gn1, n = 1307). Cohort 2 included all cycles from women seeking fertility treatments at the same center that conceived following CC/IUI treatments (CC2, n = 686). EMT was compared between groups (CC1 vs. Gn1, CC1 vs. CC2). Participants/materials, setting, methods: Outcome measures: Primary: EMT (mm). Secondary: HCG-positivity (pos-HCGR), clinical pregnancy (CPR), and spontaneous abortion rates (SABR). Statistics: Regression analysis was used to calculate Odds Ratios (OR) with associated 95% confidence intervals (95%CI), adjusting for potential confounders [maternal age, Body Mass Index (BMI), prior parity, day of EMT measurement relative to trigger). Generalized estimating equations (GEE) model were utilized to account for multiple cycles per patient. P < 0.05 was considered significant. Main results and the role of chance: In cohort 1, despite CC1 exhibiting non-inferior ovarian response compared to Gn1 (as assessed by preovulatory follicular number), EMT was significantly thinner in CC1 compared to Gn1 [Median(IQR): 7.0(5.7-8.3) vs. 8.9(7.4-10.0), p<.001]. When CC1 was compared to CC2 (CC conceiving), EMT was also thinner [Median(IQR): 7.0(5.7-8.3) vs. 7.5(6.2-9.0), for CC1 vs. CC2, respectively, p<.001]. A higher percentage of CC1 compared to Gn1 cycles resulted in EMT≤7mm (48.9% vs. 16.7%, for CC1 vs. Gn, respectively; p<.001). Most subsequent Gn cycles (82.8%), in the same women, resulted in thicker EMT compared to CC1. AdjOR, in generalized linear mixed models, suggested that CC2 when compared to CC1 cycles had thicker EMT [adjOR(95%CI): 1.81, (1.41, 2.35), p<.001]. Interestingly, clinical pregnancies were observed even when EMT was ≤4mm in both CC2 and Gn1 groups and SABR did not differ between cycles with EMT≤4mm and the ones with thicker EMT (2.5% vs. 11.5%, p=.258, in CC2; 0% and 12.3%, p=.544, in Gn1; SABR EMT ≤4 vs. 4 mm, respectively). GEE models suggested an association between EMT and CPR in CC cycles (CC1&CC2), [adjOR(95%CI): 1.12(1.07, 1.18), p<.001)] while in Gn1, no such association was observed. Limitations, reasons for caution: Our study was limited by its retrospective design. Reflecting our selection criterion, in cohort 1, most CC cycles did not result in pregnancy, restricting relevant comparisons. Number of cycles resulting in EMT ≤7mm, and particularly ≤4mm, was limited, and consequently respective results should be interpreted cautiously. Wider implications of the findings: Utilizing patients as their own controls, we showed that CC compared to gonadotropins resulted in thinner endometrium. Given comparable follicular response, and potentially estradiol levels, thinner endometrium might have resulted from CC's anti-estrogenic effect. Furthermore, patients conceiving on CC had a thicker endometrium compared to the ones that did not. Trial registration number: NA